2017
DOI: 10.1037/hea0000529
|View full text |Cite
|
Sign up to set email alerts
|

The impact of medication nonadherence on the relationship between mortality risk and depression in heart failure.

Abstract: Objective Heart failure affects over 5 million U.S. adults and approximately 20% of individuals with heart failure experience depressive symptoms. Depression is detrimental to prognosis in heart failure, conferring approximately a 2-fold increase in mortality risk. Medication non-adherence may help explain this relationship, as depressed patients are less likely to adhere to the medication regimen. Methods Depression, electronically-monitored medication adherence, and mortality were measured in a sample of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 56 publications
2
31
0
2
Order By: Relevance
“…29 However, it was lower than that (50.7%) reported by Bhatt et al 30 The variation in prevalence may be attributed to the different screening tools and illness severity. Since depressive symptoms contribute to the increase in patients' hospitalizations, readmissions and mortality, and poor health-related quality of life, [7][8][9] it is essential to recognize and manage the depressive symptoms in patients with heart failure. This study showed that illness perceptions mediated the relationship between physical symptoms and depressive symptoms in heart failure patients, consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 However, it was lower than that (50.7%) reported by Bhatt et al 30 The variation in prevalence may be attributed to the different screening tools and illness severity. Since depressive symptoms contribute to the increase in patients' hospitalizations, readmissions and mortality, and poor health-related quality of life, [7][8][9] it is essential to recognize and manage the depressive symptoms in patients with heart failure. This study showed that illness perceptions mediated the relationship between physical symptoms and depressive symptoms in heart failure patients, consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…6 Depressive symptoms have been found to contribute to increasing hospitalizations, readmissions and mortality and to a reduction in health-related quality of life in patients with heart failure. [7][8][9] To manage depressive and physical symptoms, it is essential to identify modifiable associated factors and the underlying mechanism between them in patients with heart failure.…”
mentioning
confidence: 99%
“…Nonadherence to medication is related to several factors including a higher prevalence of chronic diseases, polypharmacy, and age-related physical and mental capabilities [ 5 ]. Disease severity may improve treatment adherence [ 28 ] whereas certain comorbidities such as depression, cognitive impairment or high blood pressure increase the risk of nonadherence [ 29 , 30 , 31 ]. In our study, there were significantly more changes when the patient had cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Повышение значимости роли пациента в лечебном процессе, его активное в нем участие в настоящий момент актуально и для кардиохирургической клиники, поскольку успешность восстановления больного после хирургического вмешательства на сердце и коронарных артериях, а также длительность эффекта от него напрямую зависят от того, будет ли пациент воспринимать свою болезнь всерьез и следовать рекомендациям врачей (Wu, Frazier, Rayens et al 2013;Gathright, Dolansky, Gunstad et al 2017). При этом, согласно статистике Европейского общества кардиологов, смертность от ишемической болезни сердца (ИБС) в России -одна из самых высоких в Европе (Townsend, Wilson, Bhatnagar et al 2016).…”
Section: всемирная организация здравоохраненияunclassified